Unidades de internação de menores infratores em Goiás e a distribuição geográfica dos cases: insuficiência em face da demanda - Gonçalves, Luciano Marcio (2018)
Public security today has been the focus of debate in the most diverse nuclei of knowledge. The involvement of young people in crime, in the same way, becomes an increasingly recurring subject in the field of political, economic, social and legal sciences. This is a problem of social interest and requires attention of all. The units of hospitalization of juvenile offenders in Goiás are analyzed. The relationship between the geographic disposition of Cases in Goiás and the need for local demand is investigated. It is pointed out the difficulties related to the distance of the Cases in relation to the locality of the infractional practice, committing to the maintenance of the affective ties of the offender with the family. It is shown the importance of understanding the need for changes, inserting new proposals for intervention and restructuring the geographic distribution of the socio-educational system of minors in Goiás. A bibliographic research, associated with a field study, is applied. interviews directed to 4 sample subjects, it is observed that there is a disregard of the state authorities regarding the implementation of the Sinase Care Center, evidencing a dissociation between the local reality and the protective legislation. It is concluded that there is a need for the implementation of planned strategic actions, re-adjusting the geographic arrangement of the Socio-educational Assistance Centers in Goiás.